THE CHALLENGES IN HIGHER EDUCATION INSTITUTIONS IN INDONESIA: ARE WE ENTREPRENEURIAL UNIVERSITY YET? - Eko Sakapurnama; Martani Huseini; Pantius Drahen Soeling (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2019)
Today, the world has entered the industry revolution 4.0 era. It is inevitable that higher education institutions become the agents of change of civilizations that support the phenomenon. Some conceptions related to knowledge-based economy, entrepreneurial university or third-generation university, became the frame of thinking of experts who encourage university policies and strategies. This literature review is intended as an analysis on the current condition of higher education institutions in Indonesia, especially Universitas Indonesia and Universitas Gajah Mada, both of which are leading universities in Indonesia. As a state-owned university that is given an autonomy, the government restricts their subsidy, and this has put both state-owned universities (PTNBH) in a dilemma in an attempt to implement their Tri Dharma's activities, mainly because unclear policy to get the financial income from non-educational costs. This article will highlight some thoughts related to entrepreneurial universities, such as definitions, transformation models, and challenges to become entrepreneurial universities.